Boosting MSME Growth in Indonesia Through E-Payment Adoption: Mendorong Pertumbuhan UMKM di Indonesia Melalui Adopsi Pembayaran Elektronik - Rafisar, Ahdaniati; Prapanca, Detak (Indonesian Journal of Innovation Studies, 2024)
Technological advancements have enhanced information access, leading to innovations in financial technology such as e-payment systems. This study investigates the impact of a less cash society, perceived convenience, and trust on MSMEs’ (Micro, Small, and Medium Enterprises) intention to adopt e-payment in Sidoarjo. Using purposive sampling and the Slovin formula, data were collected from 100 respondents and analyzed with SEM-PLS. Results show that all three factors significantly influence the adoption of e-payment systems. These findings highlight the benefits of e-payment services and emphasize the need for service providers to promote ease of use and security, and for policymakers to establish protective regulations to encourage adoption. Highlight: Impact Factors: Key factors include less cash society, convenience, and trust. Methodology: Data from 100 MSMEs analyzed using SEM-PLS. Implications: Emphasize ease of use, security, and protective regulations. Keyword: Financial technology, e-payment, MSMEs, less cash society, trust